Coterminous Uppercut: An Analysis of Boxing Metaphors in Selected Ghanaian Political Cartoons - George Boakye-Yiadom (Universitas Sanata Dharma, 2025)
This study examines the use of boxing metaphors by Ghanaian political cartoonists to communicate socio-political issues, with a particular focus on the depiction of election outcomes and the portrayal of heated arguments or legal disputes. In order to gain a representative sample, ten political cartoons related to boxing scenes were downloaded from Tilapia of 3 News and Akosua of the Daily Guide. In terms of the theoretical framework that informs this study, Lakoff and Johnson's conceptual metaphor theory (CMT) and Fauconnier and Turner's conceptual blending/integration theory (CBT) are employed in conjunction with Šorm and Steen's VISMIP for the purposes of analysis. The application of CMT to the data led to the identification of conceptual metaphors such as